Urinary and serum biomarkers of renal injury in coronary artery bypass grafting: a prospective evaluation with new biomarkers’ - Antônio Felipe Leite Simão; Gdayllon Cavalcante Meneses; Lia Cavalcante Cezar; Letícia Machado de Araújo; Alice Maria Costa Martins; Heraldo Guedis Lobo Filho; Bruna Viana Barroso Martins; Geraldo Bezerra da Silva Júnior; Elizabeth De Francesco Daher; José Glauco Lobo Filho (Brazilian Journal of Nephrology, 2025)
Abstract Introduction: Cardiopulmonary bypass (CPB) for coronary artery bypass grafting (CABG) often causes kidney dysfunction and increases morbidity and mortality. Aims: To evaluate the effects of CPB on kidney structures of patients submitted to CABG using serum and urinary biomarkers. Methods: This prospective study included patients who underwent CABG over a 14-month period. Data related to clinical, surgical, and laboratory were collected. The glomerular filtration rate was estimated using the CKD-EPI equation. The urinary biomarkers trialed were nephrin, KIM-1, MCP-1, Syndecan-1, and NGAL. Results: Out of 30 patients enrolled, 22 were assessed. The mean age was 65 years and most were male. During CABG, the On-pump group had increased urinary nephrin (p = 0.007) and urinary (p = 0.036) and serum NGAL (p = 0.030) levels compared to the Off-pump group. Moreover, intraoperatively, in the On-Pump clusters, the urinary NGAL was correlated with the decrease of glomerular filtration rate in the first 48 hours after CABG (Rho = − 0.838, p = 0.009). There was no statistical difference in clinical and surgical aspects between groups according to use of CBP during CABG. Conclusion: CBP procedure used during CABG was associated with relevant effects on kidney structure, such as podocyte and tubular injury. Urinary NGAL was able to predict an impairment of glomerular filtration 48 hours after CABG.